Annona Muricata L. extract restores renal function, oxidative stress, immunohistochemical structure, and gene expression of TNF-α, IL-β1, and CYP2E1 in the kidney of DMBA-intoxicated rats - Zeweil, Mohamed M.; Khafaga, Asmaa F.; Mahmoud, Sahar F.; Wasef, Lamiaa; Saleh, Hamida; Elrehim, Attaa. M. Abd; Bassuoni, Naglaa F.; Alwaili, Maha Abdullah; Saeedi, Nizar H.; Ghoneim, Hanan A. (Frontiers in Pharmacology, 2024)
Introduction: 7,12-dimethylbenz (a) anthracene (DMBA) is a harmful polycyclic aromatic hydrocarbon derivative known for its cytotoxic, carcinogenic, and mutagenic effects in mammals and other species. Annona muricata, L. (Graviola; GRV) is a tropical fruit tree traditionally well-documented for its various medicinal benefits. This investigation is the first report on the potential antioxidant and antinfammatory reno-protective impact of GRV against DMBA-induced nephrotoxicity in rats. Methods: Forty male albino rats were allocated into four equal groups (n = 10). The 1st group served as the control, the 2nd group (GRV) was gastro-gavaged with GRV (200 mg/kg b.wt), the 3rd group (DMBA) was treated with a single dose of DMBA (15 mg/kg body weight), and the 4th group (DMBA + GRV) was gastro-gavaged with a single dose of DMBA, followed by GRV (200 mg/kg b.wt). The GRV administration was continued for 8 weeks. Results and Discussion: Results revealed a significant improvement in renal function, represented by a decrease in urea, creatinine, and uric acid (UA) in the DMBA + GRV group. The antioxidant potential of GRV was confirmed in the DMBA + GRV group by a significant decline in malondialdehyde (MDA) and a significant increase in catalase (CAT), superoxide dismutase (SOD), glutathione S transferase (GST), and reduced glutathione (GSH) compared to DMBA-intoxicated rats; however, it was not identical to the control. Additionally, the antiinflammatory role of GRV was suggested by a significant decline in mRNA expression of cytochrome P450, family 2, subfamily e, polypeptide 1 (CYP2E1), tumor necrosis factor-alpha (TNF-α), and interleukin 1 beta (IL-1β) in the DMBA + GRV group. Moreover, GRV improved the histopathologic and immunohistochemical expression of TNF-α, CYP450, and IL1β in DMBA-intoxicated kidney tissue. Conclusively, GRV is a natural medicinal product that can alleviate the renal injury resulting from environmental exposure to DMBA. The reno-protective effects of GRV may involve its anti-inflammatory and/or antioxidant properties, which are based on the presence of phytochemical compounds such as acetogenins, alkaloids, and flavonoids.